2020
DOI: 10.3390/antibiotics9040167
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance and Persister Formation in Oral Streptococci

Abstract: The aim of this study was to analyze the potential influence of long-term exposure in subinhibitory concentrations of chlorhexidine on the emergence of tolerant and/or persistent cells in oral streptococci. The two oral streptococcal isolates S. mutans ATCC25175 and S. sobrinus ATCC33402 were incubated, after long-term subinhibitory exposure to chlorhexidine, in liquid growth media containing high concentrations of chlorhexidine. A distinct subpopulation of more chlorhexidine-tolerant cells could be detected i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 41 publications
(56 reference statements)
1
6
0
Order By: Relevance
“…Although total eradication of S. aureus biofilms was not achieved during Sb‐1 treatment, this study reinforced previous findings that phage therapy may be used as adjunctive therapy to conventional antibiotics because bacteriophages, such as Sb‐1 target, degrade the barriers, which lowers the efficacy of antibiotics 163‐165 . Identifying bacteriophages similar to Sb‐1 may become critical if effective phage therapy are developed for oral biofilms as antibiotic‐tolerant bacteria, and persister cells become more established in dental plaque 101,152,166,167 …”
Section: Bacteriophage‐mediated Biofilm Dynamicssupporting
confidence: 79%
See 1 more Smart Citation
“…Although total eradication of S. aureus biofilms was not achieved during Sb‐1 treatment, this study reinforced previous findings that phage therapy may be used as adjunctive therapy to conventional antibiotics because bacteriophages, such as Sb‐1 target, degrade the barriers, which lowers the efficacy of antibiotics 163‐165 . Identifying bacteriophages similar to Sb‐1 may become critical if effective phage therapy are developed for oral biofilms as antibiotic‐tolerant bacteria, and persister cells become more established in dental plaque 101,152,166,167 …”
Section: Bacteriophage‐mediated Biofilm Dynamicssupporting
confidence: 79%
“… 163 , 164 , 165 Identifying bacteriophages similar to Sb‐1 may become critical if effective phage therapy are developed for oral biofilms as antibiotic‐tolerant bacteria, and persister cells become more established in dental plaque. 101 , 152 , 166 , 167 …”
Section: Bacteriophage‐mediated Biofilm Dynamicsmentioning
confidence: 99%
“…Most insights in persistence have been gathered using Gram-negative bacteria, like E. coli, S. typhimurium and P. aeruginosa (8, 10, 11, 18). However, different studies already indicated a role for persistence in Gram-positive bacteria as well (18, 5355), and more specifically in various reports on streptococcal species (18, 56). Persisters in S. mutans , a cariogenic oral bacterium, are tolerant to a wide variety of antibiotics (57), but also to a dental caries defensive agent, dimethylaminododecyl methacrylate (DMADDM) (58), and to other antibacterial monomers used in dental medicine (59).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, once in the EPS matrix, oral bacteria are protected from microenvironmental damage, from the host's immune defenses and from antimicrobial agents [47]. The presence of persistent dormant cells in the biofilm is crucial, given their high tolerance to antimicrobial agents, reason why they are pointed out as the main parties responsible for the biofilm recalcitrancy to these agents [48].…”
Section: Oral Biofilm Formationmentioning
confidence: 99%